The children's discovery Bible : discovering God's word for the first time - Hiebert, Charlene; Rose, Drew (Colorado Springs, CO : Chariot Victor Pub., 1996)
A collection of retold stories and memory verses from the Bible.
"Read to me: ages 3-6, read it myself: ages 5-8"--Cover.
Keywords: Bible stories, English; Bible stories